2015
DOI: 10.1002/jsfa.7186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different maturity stages and growing locations on changes in chemical, biochemical and aroma volatile composition of ‘Wonderful’ pomegranate juice

Abstract: Knowledge on the impact of fruit maturity and agro-climatic locations (with different altitudes) on biochemical and aroma volatile attributes of pomegranate fruit provides a useful guide for selecting farm location towards improving fruit quality and the maturity stage best for juice processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 38 publications
(88 reference statements)
3
37
0
Order By: Relevance
“…Wonderful) was harvested at commercially ripened stage with characteristic deep-red skin and deep-red arils with mature kernels (Mphahlele et al, 2015), from Houdconstant Farm, Porterville, Western Cape (33 01 0 00 00 S, 18 59 0 00 00 E), South Africa. Fruits were sorted, cleaned and minimally processed at the farm pack house.…”
Section: Sample Preparation and Packagingmentioning
confidence: 99%
“…Wonderful) was harvested at commercially ripened stage with characteristic deep-red skin and deep-red arils with mature kernels (Mphahlele et al, 2015), from Houdconstant Farm, Porterville, Western Cape (33 01 0 00 00 S, 18 59 0 00 00 E), South Africa. Fruits were sorted, cleaned and minimally processed at the farm pack house.…”
Section: Sample Preparation and Packagingmentioning
confidence: 99%
“…This knowledge could allow for determination of the optimal harvest time for obtaining the maximum nutritional properties. Other studies on the chemical composition of fruits have also found significant variations in growing locations (Mphahlele et al, 2014;2016), phenolic compounds (Gil et al, 2000;Tzulker et al, 2007;Gómez-Caravaca et al, 2013;Fischer et al, 2013a;Li et al, 2015), sugars (Mphahlele et al, 2016), antioxidant activity (Borochov-Neori et al, 2009;Tehranifar et al, 2010;Zaouay et al, 2012), and mineral composition (Mirdehghan and Rahemi, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Over the last decade, the area used for pomegranate cultivation and production in Chile has increased significantly, passing of a cultivated area of 250 ha in 2007 to 1150 ha in (ODEPA, 2015. This increase is attributed to the rise in popularity of the pomegranate fruit in recent years due to the functional properties of its phenolic compounds, including phenolic acids, flavonoids (anthocyanins), condensed tannins (proanthocyanidins) and hydrolyzable tannins (ellagitannins and gallotannins) (Li et al, 2015;Mphahlele et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that more than 500 pomegranate cultivars have been studied regarding their physicochemical index, nutrient composition and value, and sensory attributes (Mayuoni‐Kirshinbaum & Porat, ). These studies were mainly focused on the influences of genotype and environmental conditions on the accumulation of nutrients, such as sugar and acid, polyphenol, anthocyanin, and vitamin C (Beaulieu et al, ; Hernández, Legua, Martínez, Melgarejo, & Martínez, ; Legua et al, ; Li et al, ; Mditshwa et al, , Mphahlele, Caleb, Fawole, & Opara et al, ; Mphahlele, Stander, Fawole, & Opara, ; Tzulker et al, ). In the meantime, their antioxidant capacity of pomegranate was also investigated (Tzulker et al, ; Schwartz et al, ).…”
Section: Introdcutionmentioning
confidence: 99%
“…C (Beaulieu et al, 2015;Hern andez, Legua, Martínez, Melgarejo, & Martínez, 2014;Legua et al, 2016;Li et al, 2015;Mditshwa et al, 2013, Mphahlele, Caleb, Fawole, & Opara et al, 2016Mphahlele, Stander, Fawole, & Opara, 2014;Tzulker et al, 2007). In the meantime, their antioxidant capacity of pomegranate was also investigated (Tzulker et al, 2007;Schwartz et al, 2009).…”
mentioning
confidence: 99%